La nueva historia intelectual frente a la historia de las ideas: algunas simplificaciones críticas (2022)
This research article presents the criticisms that intellectual history, in its version of history of political languages, makes to the history of ideas. The background of both historiographies is presented and it analyzes how the criticism made by the intellectual history incurs in theoretical simplifications, where the history of ideas is reduced to the capture of the peculiarity and originality of ideas in Latin America, neglecting its political purposes, its commitment to the knowledge of the region and its commitment to decolonization and emancipation. It is argued that the type of analysis carried out by intellectual history questions the philosophical character and depoliticizes the history of ideas. It is concluded that, although the approach to the history of political languages allows the analysis of an interesting set of problems, it is not a matter of one historiographic model being replaced by another, but of the coexistence of epistemic and methodological pluralism. The methodology used for the research is textual hermeneutics.